Synthesis, Characterization and Thermal Studies of Rh(III) Complexes Derived from Bidentate Schiff Bases - Disale, Sameer; Pawanoji, Aniket; Mehta, Bipin (Asian Journal of Chemistry, 2010)
The Schiff base ligands were derived from 2-hydroxy-3-methoxybenzaldehyde (HL1), 4- hydroxy-3-methoxybenzaldehyde (HL2), with p-toluidine and 3-hydroxybenzaldehyde with 4- hydroxybenzhydrazide (HL3) and 3-hydroxy-2-naphthoic hydrazide (HL4). The Rh(III) metal complexes of these Schiff base ligands have been synthesized and characterized by IR, electronic, 1H NMR spectra as well as by elemental analysis, thermogravimetry, molar conductance and magnetic susceptibility measurements. IR and 1H NMR data shows that all the Schiff bases behave as bidentate and coordinated to Rh(III) via nitrogen and oxygen.